`Every run is hard`: endurance athletes` experiences of return to sports participation after COVID-19 - a mixed methods study - Haley, C. A.; Van Aswegen, H.; Olivier, B. (Translational Sports Medicine, 2024)
Protracted return to sport (RTS) following COVID-19 is common due to long-term cardiopulmonary symptoms and persistent fatigue. In athletes, low exercise tolerance may result in emotional distress. The aim of this study is to assess the symptom severity, the management thereof and the impact on quality of life (QOL) as endurance athletes return to their preillness level of sports participation. A cross-sectional survey-based mixed methods study of long-distance athletes was performed. Quantitative data included sport and disease characteristics, fatigue score and management of persistent symptoms. A total of 295 survey responses were included. The mean age was 45.1 (10.2) years and 54.7% were male. Barriers to exercise included tachycardia (72%), fatigue (72%), dyspnoea (58%) and inability to exercise at high intensities (75%). High physical and mental fatigue scores were found, the former significantly predicting return to sport. Qualitative data were collected through open-ended questions exploring challenges faced when returning to sport post-COVID-19 convalescence and the impact on their QOL. Biopsychosocial well-being constituted three themes: Physical, Psychological and Social. Categories with high code frequencies included persistent cardiopulmonary symptoms, physical fatigue, emotional distress and social disengagement. Mixing the methods revealed that the athletes` QOL deteriorated due to protracted RTS after COVID-19. A multidisciplinary approach to management may be required by endurance athletes.